The Science Feature in Acehnese Tafseer: a Comparative Study between As-Sinkily’s and As-Shiddiqie’s Works - Ramli, Angraini; Elatrash, Radwan Jamal Yousef (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
The development of modern science was followed by the development of scientific findings as well. Interestingly, many scientific facts are found in the Quran which existed even before modern science developed. In responding to the verses that contain scientific facts, several commentators have also included these scientific facts in their works. This article aims to further examine two interpretations of the Quran originating from Aceh, Turjuman al-Mustafid which belongs to As-Singkily, and Tafseer al-Quran al-Majid an-Nur by As-Siddiqie. By using qualitative methods and descriptive and content analysis approaches, this research found that both scholars As-Singkily and As-Siddiqie accepted the scientific facts contained in the Quran. These facts can be seen from their works which mentioned scientific facts along with their commentaries. A science feature was found more in As-Siddiqie’s work which was written and published in the 20th century compared to as-Singkily’s work which was published in the 18th century.